Frontispiece: High‐Throughput Isolation of Cell Protrusions with Single‐Cell Precision for Profiling Subcellular Gene Expression. Issue 39 (24th September 2019) - Zhang, Pengchao; Han, Xin; Yao, Jun; Shao, Ning; Zhang, Kai; Zhou, Yufu; Zu, Youli; Wang, Bin; Qin, Lidong
Abstract : Microfluidics The isolation of cell protrusions at the single‐cell level for profiling subcellular gene‐expression levels can be realized using the microfluidic platform reported by B. Wang, L. Qin, et al. in their Communication onpage 13700 ff.